2008
DOI: 10.1016/j.ijantimicag.2008.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Aloe-emodin is an interferon-inducing agent with antiviral activity against Japanese encephalitis virus and enterovirus 71

Abstract: In this study, aloe-emodin was identified as a potential interferon (IFN)-inducer by screening compounds from Chinese herbal medicine. Aloe-emodin showed low cytotoxicity to human HL-CZ promonocyte cells and TE-671 medulloblastoma cells and significantly activated interferon-stimulated response element (ISRE) and gamma-activated sequence (GAS)-driven cis-reporting systems. Moreover, aloe-emodin upregulated expression of IFN-stimulated genes such as dsRNA-activated protein kinase and 2',5'-oligoisoadenylate syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 12 publications
1
58
0
3
Order By: Relevance
“…Our prior study proved quercetin an active antienterovirus component of K. gracilis leaf extract, showing IC 50 values above 117  μ M for EV71 and 176  μ M for CoxA16 [14]. Eupafolin was thus suggested as crucially active antienterovirus component in K. gracilis , at the same time showing similar anti-EV71 efficacy and selectivity with identified potential anti-EV71 compounds of natural products like allophycocyanin, aloe-emodin, gallic acid, chrysosplenetin, and penduletin [1720]. …”
Section: Discussionmentioning
confidence: 92%
“…Our prior study proved quercetin an active antienterovirus component of K. gracilis leaf extract, showing IC 50 values above 117  μ M for EV71 and 176  μ M for CoxA16 [14]. Eupafolin was thus suggested as crucially active antienterovirus component in K. gracilis , at the same time showing similar anti-EV71 efficacy and selectivity with identified potential anti-EV71 compounds of natural products like allophycocyanin, aloe-emodin, gallic acid, chrysosplenetin, and penduletin [1720]. …”
Section: Discussionmentioning
confidence: 92%
“…Emodin has been previously reported to possess antiviral [16], antiinflammatory [17], antiulcerogenic [18], immunosuppressive [19], and chemopreventive activities [20]. Interestingly, antiproliferative effects of emodin have been observed in many tumor cell lines, including HER2/neuoverexpressing breast cancer [21], lung cancer [22], leukemia [23], HCC [24], and neuroblastoma [25] but not in normal cells, suggesting that emodin may have a significant therapeutic efficacy as an anticancer agent.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated the antiviral activity of type I IFNs against EV71 infection in vitro and in vivo (25,26). Furthermore, treatment with an IFN-inducing agent (27) and synergistic inhibition of EV71 replication by IFN-␣ and rupintrivir (28) have been identified as effective treatment regimens. However, during EV71 infection, several immune escape strategies are elicited by EV71 to attenuate the type I IFN response.…”
mentioning
confidence: 99%